Investment in Energy Projects with Private Participation Remained at a Peak Level But Was Highly Concentrated in 2010 - Perard, Edouard (World Bank, Washington, DC, 2012)
In 2010, 106 energy projects with private participation reached financial or contractual closure in 28 low- and middle-income countries, involving investment commitments of US$55.7 billion. In addition, energy projects implemented in 1990-2009 attracted new investment of US$14.2 billion, bringing total investment commitments to the energy sector to US$69.9 billion in 2010. Such level of activity represents a 4 percent drop by investment and a 25 percent decline by the number of projects from 2009. Private activity in energy remained close to a peak level in 2010. However, such activity was highly concentrated on a few countries. India alone attracted 54 percent of investment in the sector and 34 percent of new projects, and was the country that sustained investment in energy close to a peak level. If India were excluded, investment in energy in developing countries would have fallen by 50 percent in 2010 compared with 2009. In addition, the four top countries (adding Brazil, Russian Federation, and Turkey to the list) accounted for 77 percent of investment and 58 percent of new projects. By type of business, private activity remained highly concentrated on electricity generation projects, which accounted for 75 percent of investment and 82 percent of new projects in 2010.